Karakteristik Ibu Hamil Kurang Energi Kronis di Puskesmas Gesang, Lumajang Tahun 2020: Analisis Deskriptif - Mita Prisabela; Siti Rahayu Nadhiroh; Emyr Reisha Isaura (Media Gizi Kesmas, 2023)
Background: Basic Health Research conducted by Ministry of Health in 2018 stated that the prevalence of chronic energy deficiency pregnant women in Indonesia reached 17,3%. Chronic Energy Deficiency conditionsin pregnant women can have an impact to miscarriages, premature babies, babies born with disabilities, and also low birth weight babies which can affect stunting in the future. The prevalence of LBW in Indonesia is 6,2%, in East Java province is 3,7%, and in Lumajang is 4,9%. Objectives: The purpose of this study is to obtain a description of the characeristics of pregnant women with chronic energy deficiency in Gesang Health Center, Lumajang working area in 2020. Methods: This research is a descriptive analysis study that uses secondary data with a population of all pregnant women in the working area of Gesang Health Center, Lumajang in 2020 and the sampling technique is a total sample of 49 people pregnant women with chronic energy deficiency. Results: The results showed that 65,3% of pregnant women with chronic energy deficiency belonged to non-risk age category which is 20-35 years,the majority of CED pregnant women's gestational age is in 2nd and 3rd trimesters each had a percentage of 38,8%, most of the pregnant women with CED do not experience anemia (87,8%), the gravida status of the highest CED pregnant women is primigravida (71,4%), most of CED pregnant women in the first pregnancy or in 0 months gestational distance (71,4%) and 61,2% CED pregnant women had normal nutritional status. Conclusions: Based on this research, it can be concluded that the characteristics of pregnant women with chronic energy deficiency (CED) in the working area of Gesang Health Center, Lumajang are maternal age, gestational age, anemia status, gravida, pregnancy interval, and maternal nutritional status.